2016
DOI: 10.1111/nep.12752
|View full text |Cite
|
Sign up to set email alerts
|

Combining intra‐dialytic exercise and nutritional supplementation in malnourished older haemodialysis patients: Towards better quality of life and autonomy

Abstract: Protein-energy wasting (PEW), defined as a loss of body protein mass and fuel reserves, is a powerful predictor of adverse outcomes in haemodialysis (HD) patients. Robust arguments suggest that intra-dialytic exercise, combined with oral/parenteral nutrition, enhances the effect of nutritional interventions in HD patients. This pilot randomized controlled trial investigated the feasibility and the effects of a 6 month intra-dialytic cycling program combined to a nutritional support on PEW, physical functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 19 publications
1
48
0
2
Order By: Relevance
“…The Dietary Recommendations for Chronic Dialysis Patients published by the Japanese Society for Dialysis Therapy 2014 also recommend an energy intake of 30-35 kcal/kg and protein intake of 0.9-1.2 g/kg [42]. However, a study demonstrated that the physical function and QOL were significantly improved in patients with PEW by a combination of nutritional and exercise therapies compared with nutritional therapy alone [43], thus nutritional and exercise therapies are complementary to each other.…”
Section: Lifestyle Modification Dietary Counseling and Medicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Dietary Recommendations for Chronic Dialysis Patients published by the Japanese Society for Dialysis Therapy 2014 also recommend an energy intake of 30-35 kcal/kg and protein intake of 0.9-1.2 g/kg [42]. However, a study demonstrated that the physical function and QOL were significantly improved in patients with PEW by a combination of nutritional and exercise therapies compared with nutritional therapy alone [43], thus nutritional and exercise therapies are complementary to each other.…”
Section: Lifestyle Modification Dietary Counseling and Medicationsmentioning
confidence: 99%
“…4) (Fig. 6) [43,69,[71][72][73][74][75][76], and Kt/V (MD 0.07, 95% CI 0.01-0.14) ( Fig. 7) [43,66,67,71,[77][78][79].…”
Section: Positions Of Exercise Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional therapies such as enteral nutrition, parenteral nutrition, and oral nutritional supplementation can be used to treat PEW [1]. A list of these studies, along with their reported nutritional outcomes, is provided in Table 1 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The studies designed to establish the benefits of nutritional supplementation on the long-term improvements in overall nutritional status in hemodialysis patients with PEW have yielded encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…One reason may be the age of patients with ESRD, a vulnerable population at high risk of mortality. Now more than ever, whether for paediatric patients4 or older patients (>65 years of age),5 let's challenge this intrinsic reluctance by advocating intradialytic exercise programmes as part of the standard care for patients receiving dialysis.…”
mentioning
confidence: 99%